Design Effect of Metallic (Durable) and Polymeric (Resorbable) Stents on Blood Flow and Platelet Activation. Issue 12 (5th September 2018) - Marom, Gil; Eswaran, Senthil K.; Rapoza, Richard J.; Hossainy, Syed F. A.; Slepian, Marvin J.; Bluestein, Danny
Abstract: Bioresorbable vascular scaffolds (BVS) provide transient vessel support for occluded coronary arteries while resorbing over time, potentially allowing vessel restoration approximating the native, healthy state. Clinical trials indicate that the Absorb BVS (Abbott Vascular, Santa Clara, CA) performance was similar to that of the Xience metallic drug‐eluting stent (DES), with low long‐term complications rates. However, when under‐deployed in very small vessels (diameter < 2.25 mm), the thrombosis rate of BVS was higher, possibly due to the effect of strut thickness on the hemodynamics (157 μm BVS vs. 81 μm DES). This study aims to determine the influence of BVS design in vessels of varying diameter on the potential platelet activation. Sixteen computational fluid dynamics models of vessels of varying diameter (1.8–3.0 mm), strut thickness (81–157 μm), and BVS/DES designs were compared. Platelet stress accumulation (SA), a metric for the activation potential, was calculated along platelet flow trajectories and their probability distribution was compared. The models were consistent with clinical observations, indicating that devices deployed in very small vessels exhibited increased probability for platelet activity as compared to the same devices deployed in nominal sized vessels. Deployment, although with residual stenosis, increased probability for higher SA than in similar diameter straight vessels. Reducing BVS struts thickness while maintaining their pattern improved performance closer to that of DES. Our findings highlight the importance of appropriate vessel sizing and deployment technique for BVS, and may help designing future BVS with thinner struts, ultimately improving performance in very small vessels.